Spirituality Meets Civic Engagement - Markham, Ian (Implicit Religion, 2009)
This paper starts with David Hay’s data about the vast increase over the last fifteen years in people in the UK having religious experiences. This data confirms the underlying religious dispositions of the British, although there is clearly a significant decline of participation in religious institutions. However, as many have noted, religious organizations are amongst the strongest in civic society (more people are in church than are involved in political parties). So we need to tap into the spiritual motivation to encourage a range of participation in civic society, from Boy Scouts to Rotary. The American sociologist Nancy Ammerman has shown that the more a person is involved in one organization the more they end up being involved in lots of organizations. Therefore spirituality is an important basis for civic engagement.